Evaluasi Program Jaminan Kesehatan Masyarakat Miskin (JKMM) Bagi Masyarakat Kurang Mampu Pada Dinas Sosial Kabupaten Sidoarjo - Ratnawati, Susi; Ismail, Ismail; Mellyasari, Novalita Puteri (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2023)
The purpose of this study was to evaluate the existing Health Insurance program in the city of Sidoarjo. Because Sidoarjo City is still high in poverty level of its people, therefore the Sidoarjo City Government created a Health Insurance program. With the existence of free health services in the form of Poor People's Health Insurance (JKMM), which aims to alleviate poverty and help the economy and the burden of underprivileged people in meeting their needs. The JKMM program is only intended for people who live in Sidoarjo, because not all districts have the same program because districts have their own policies. This type of research is qualitative research, by obtaining data sources through interviews and documentation. The Poor People's Health Insurance Program (JKMM) lacks widespread information so that many Sidoarjo people still do not know and there are still many who have not received health insurance assistance. Among the various obstacles to this JKMM program, there is also support from the Sidoarjo City Government.